2009
DOI: 10.1111/j.1462-2920.2008.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing microbial diversity in production water from an Alaskan mesothermic petroleum reservoir with two independent molecular methods

Abstract: The phylogenetic diversity of Bacteria and Archaea within a biodegraded, mesothermic petroleum reservoir in the Schrader Bluff Formation of Alaska was examined by two culture-independent methods based on fosmid and small-subunit rRNA gene PCR clone libraries. Despite the exclusion of certain groups by each method, there was overall no significant qualitative difference in the diversity of phylotypes recovered by the two methods. The resident Bacteria belonged to at least 14 phylum-level lineages, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
120
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 55 publications
10
120
2
Order By: Relevance
“…A current synthesis of the available data suggests that JS1 is a characteristic denizen of subseafloor environments, and is particularly abundant in sediments associated with methane hydrates and hydrocarbon seeps, and on continental margins and shelves (Inagaki et al, 2006;Orcutt et al, 2011;Parkes et al, 2014). Sequences related to JS1 have also been detected in environments such as petroleum reservoirs (Pham et al, 2009;Kobayashi et al, 2012), hypersaline microbial mats (Harris et al, 2013), and landfill leachates (Liu et al, 2011). The phylogenetic relationships between OP9, JS1 and other bacterial phyla have not been fully resolved (McDonald et al, 2012), and to date, no axenic cultures have been reported for either of these lineages, although enrichment cultures containing JS1 have been successfully obtained (Webster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A current synthesis of the available data suggests that JS1 is a characteristic denizen of subseafloor environments, and is particularly abundant in sediments associated with methane hydrates and hydrocarbon seeps, and on continental margins and shelves (Inagaki et al, 2006;Orcutt et al, 2011;Parkes et al, 2014). Sequences related to JS1 have also been detected in environments such as petroleum reservoirs (Pham et al, 2009;Kobayashi et al, 2012), hypersaline microbial mats (Harris et al, 2013), and landfill leachates (Liu et al, 2011). The phylogenetic relationships between OP9, JS1 and other bacterial phyla have not been fully resolved (McDonald et al, 2012), and to date, no axenic cultures have been reported for either of these lineages, although enrichment cultures containing JS1 have been successfully obtained (Webster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-established scientific fact that oil reservoirs harbour and sustain diverse bacterial and archaeal communities (Zhu et al, 2003;Grabowski et al, 2005;Youssef et al, 2009, Li et al, 2006 and multiple groups of microorganisms with diverse physiological and metabolic activities and phylogenetic affiliations have routinely been recovered from oil reservoirs (Voordouw et al, 1996;Orphan et al, 2000;Green and Voordouw, 2003;Jan-Roblero et al, 2004;Magot, 2005;Li et al, 2006, Dahle et al, 2008Pham et al, 2009;Okoro et al, 2014). A comprehensive assessment of the diversity, metabolic processes and habitat conditions within a petroleum reservoir is therefore an important component of reservoir management because the knowledge gained can be useful in mitigating ahead of time potential cases of souring and biocorrosion and can also be used to improve oil production and recovery processes (Li et al, 2012;Youssef et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive assessment of the diversity, metabolic processes and habitat conditions for petroleum microorganisms is therefore of practical importance for assessing the economic potentials of oil fields. It will also help in the understanding of how in-situ biotic factors may affect oil production operations (Pham et al, 2009). A study by Van der Kraan et al (2009) have also indicated how the presence of specific microbial communities could present information on some characteristics of oil reservoir such as temperature, acidity, salinity, and redox-potential, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the environmental conditions for different oil reservoirs, such as the temperature, oil compositions, salinity, etc., could be very diverse, which may lead to significant differences in indigenous bacterial communities. For example, in the high-temperature oil reservoirs in the North Sea oil-field, the microbial community was dominated by Firmicutes (about 55%) with 20% Bacteroidetes (Hakon et al, 2008), while Proteobacteria and Firmicutes were dominant in the produced water from mesophilic oil reservoirs (Pham et al, 2009), and a single phylotype of Arcobacter was found in an oil reservoir with low temperature (Grabowski et al, 2005). Since such a substantial difference in the indigenous bacterial communities existed in different oil reservoirs, it is interesting to know how the different indigenous bacterial communities will impact the sludge bacterial communities as well as the correlations among community composition, function and wastewater treatment performance of a biological system.…”
Section: Introductionmentioning
confidence: 99%